Animal hair evidense in an 11th century female grave in Luistari, Finland - Kirkinen, Tuija; Vajanto, Krista; Björklund, Stina (Archaeological Textiles Review, 2020)
Luistari cemetery in southwestern Finland, is one of the most significant Iron Age and Early Medieval period (seventh to 15th centuries CE) sites with nearly 1,300 excavated inhumation burials. The cemetery has been of great importance for textile research because of the cloth fragments preserved in contact with metal items. The first scientific reconstruction of dress in Finland, the ancient dress of Eura, was based on finds from the 11th century female Grave 56. This paper presents the rich fur and hair finds preserved in Grave 56. The hair and fibre material was identified by their morphological features, using polarised light and scanning electron microscopy (SEM). It is suggested that fur was used for furnishing the grave and for accessories such as a knife sheath and a pouch. The possible remains of fur garments which enhance the current understanding of the outfit of the woman in Grave 56 are also discussed.